'As Hunters find their Game by the Trace': Reading to Discover in The Anatomy of Melancholy. (7th December 2018) - Gowland, Angus
Abstract: The critical edition of Robert Burton's Anatomy of Melancholy, published by the Clarendon Press between 1989 and 2000, provided an invaluable resource for Burton scholars in the form of a generally reliable reading text and extensive critical apparatus, including three volumes of commentary devoted to tracing Burton's sources, identifying historical persons, events and geographical locations mentioned in the text, and explicating obscure allusions and technical terminology. Since its publication, however, there has been little attention paid to the contents of the Clarendon commentary, which contains many lacunae and entries that invite alteration. This is particularly regrettable, because Burton aimed the Anatomy partly at scholarly readers who were expected to read his cento in a similar way to a modern literary commentator, primarily by identifying its sources and allusions, and interpreting their deployment and manipulation in the text. This article seeks to supplement the Clarendon commentary by extending and revising its treatment of bibliographical sources, persons, geographical locations, and textual explanation. In doing so, it exemplifies a mode of reading that Burton expected for his book. It concludes by considering the implications for our understanding of the intended readership of the Anatomy .